Filling ecological gaps in Chilean Central Patagonia: Patterns of biodiversity and distribution of sublittoral benthic invertebrates from the Katalalixar National Reserve waters ( 48°S) - Zapata-Hernández, Germán; Gorny, Matthias; Montiel, Américo (Frontiers in Marine Science, 2022)
Knowledge about composition, diversity and geographic distribution of marine species is important for a successful conservation planning in the future. The ecological and zoogeographical patterns of benthic communities in Central Patagonia have been scarcely studied, due to the remoteness of the area, combined with harsh weather conditions. During the past years four scientific expeditions were executed in order to know the biodiversity, ecological and biogeographical patterns of benthic invertebrates in the Katalalixar National Reserve (KNR) waters, Central Patagonia ( 48°S). Our analyses comprised images from 26 video transects using a remotely operated vehicle, completed with biological sampling at four stations by means of SCUBA diving, covering a bathymetric range from 10 to 220 m depth. Stations covered the entire longitudinal range of the KNR, from inner channels to the Pacific Ocean. A total of 187 benthic invertebrate taxa were identified as OTUs (operational taxonomic units), being the mollusks the most conspicuous taxonomic group (18.7%), followed by sponges, echinoderms (16.6% each one), and arthropods (14.4%). A higher OTU richness (42 to 51 OTUs) was observed in the central and western parts of the KNR waters. Analyses of the β-diversity indicated a similar level of species turnover between shallow, intermediate, and deep strata, as well as an important turnover between different locations. Dissimilitude in the assemblage structure of invertebrates were explained mainly by changes in substrate types and longitude. Most of the species (49%) found in the KNR waters showed a wide latitudinal distribution range along the Eastern South Pacific Ocean (ESP) and Chilean Patagonia of fjords and channels (CPFC) ( 18°S and 56°S), whereas 9.4% of the species have a wide distribution range between CPFC and the south of the Antarctic polar front (SAPF; 65°S). Since only 16.7% of the species identified in KNR are distributed exclusively in the CPFC waters, it may be considered as a transition area of marine invertebrates, distributed between northern ESP and SAPF. The knowledge of species composition and distribution patterns along spatial and environmental gradients is essential for any sustainable management, monitoring and future conservation plans to protect the fragile and diverse marine ecosystems of Chilean Patagonia.